The Effect of Fire and Rewetting on the Groundwater Level in Tropical Peatlands - Silviana, S.H.; Saharjo, B.H.; Sutikno, S.; Putra, E.I.; Basuki, I. (Springer, 2021)
Hydrological system strongly influences the sustainability of peatlands. The drainage system in peatlands that is not designed appropriately will result in the drop of groundwater level (GWL), and thus, peat will be dried and become susceptible to fire. Efforts to restore peatlands have been carried out, one of which is peat rewetting through canal blocking. This study assessed the non-burnt and burnt peatland areas as well as an area with canal blocking to determine the effect of fire and canal blocking on the GWL for the foregoing variables. In each area, dipwells were established at a distance of 1 m (representing the canal water level), 10, 50, 100, 250, and 350 m from the canal. The study clearly showed a significant correlation between the average GWL and fire, and canal blocking as well as the distance from the canal. Fire resulted to an increase of the average GWL, from 61 cm to 50 cm below the ground. There were significant impacts on land use relevant to the average GWL. Canal blocking demonstrated its role in increasing GWL on drained peat areas by mimicking the average GWL on the reference site. This study concluded that constructing more canal blockings and planting more fire-resistant plants are critical to reduce the fire risks.